Honour killing as engendered violence against women in Amit Majmudar’s Partitions (2011) - Chua, Gabriel Clement Chen Wei; Bahar, Ida Baizura; Noor, Rohimmi (Penerbit Universiti Kebangsaan Malaysia, 2016)
The 1947 Partition of British India, otherwise simply known as Partition, marked not only the births of India and Pakistan, but also one of modern history’s largest human mass migrations, in which an estimated million died and thousands of women were subjected to horrifying acts of engendered violence. Scholars, such as Menon and Bhasin (1998) as well as Butalia (2000), have conceptualised engendered violence during Partition as a violation of women’s bodies, sexualities and psyches by men in general, manifested in various forms ranging from abduction and rape to honour killing and bodily mutilations. However, this study is limited to examining how honour killing is depicted as a form of such violence in the novel Partitions (2011) by Amit Majmudar. More importantly, it examines how depictions of the honour killing of women during Partition in the selected text can also be read as manifestations of the negative underside of the concept of biopower conceptualised by Foucault, in which mass death and destruction are necessary to ensure the survival of future generations. This study reveals, based on textual evidence surrounding the botched honour killing of the character Simran Kaur, that the honour killing of women during Partition is due to the perception of the time, place and society that women, as well as their sexuality, are symbolic constructions of male honour. This subsequently leads to women being viewed by their own men-folk as threats against the honour of their respective religions and communities in times of communal strife.